Comparison of low power laser and kinesio taping for the treatment of carpal tunnel syndrome: A prospective randomized study - Akgol, Gurkan; Elbasti, Muhammet Sahin; Gulkesen, Arif; Alkan, Gokhan; Kaya, Arzu; Ulusoy, Hasan (Ios Press, 2021)
BACKGROUND: Although carpal tunnel syndrome (CTS) is a common neuromuscular disorder, studies on its conservative treatment are inadequate and contradictory. OBJECTIVES: This study aimed to investigate and compare the effectiveness of low power laser therapy (LPLT) and Kinesio taping (KT) for the treatment of CTS. METHODS: Sixty patients with CTS were included in this study. One group received 15 sessions of KT, and the second group underwent 15 sessions of LPLT within three weeks. All patients were assessed with hand grip strength (HGS), Visual Analogue Scale (VAS)-pain, Douleur Neuropathique-4 (DN4) score, Boston Questionnaire (BQ), and electroneuromyography before and after treatment. RESULTS: Before treatment, all clinical and neurophysiological parameters were similar between the groups. After treatment, both groups significantly improved in terms of HGS, VAS-pain, DN4, and BQ. However, the LPLT group had significantly better HGS, VAS-pain, DN4, and BQ than the KT group. In addition, while median nerve motor distal latency and median nerve sensory conduction velocity improved significantly with treatment in both groups, the LPLT group's improvement was significantly better than that of the KT group. CONCLUSIONS: In patients with CTS, both LPLT and KT were effective treatments. However, the LPLT group had significantly better improvements than the KT group.
Keywords: Carpal tunnel syndrome; kinesio taping; laser therapy; low power laser